Using the phospha-Michael reaction for making phosphonium phenolate zwitterions - Steiner, Matthias R.; Schmallegger, Max; Donner, Larissa; Hlina, Johann A.; Marschner, Christoph; Baumgartner, Judith; Slugovc, Christian (Beilstein Journal of Organic Chemistry, 2024)
The reactions of 2,4-di-tert-butyl-6-(diphenylphosphino)phenol and various Michael acceptors (acrylonitrile, acrylamide, methyl vinyl ketone, several acrylates, methyl vinyl sulfone) yield the respective phosphonium phenolate zwitterions at room temperature. Nine different zwitterions were synthesized and fully characterized. Zwitterions with the poor Michael acceptors methyl methacrylate and methyl crotonate formed, but could not be isolated in pure form. The solid-state structures of two phosphonium phenolate molecules were determined by single-crystal X-ray crystallography. The bonding situation in the solid state together with NMR data suggests an important contribution of an ylidic resonance structure in these molecules. The phosphonium phenolates are characterized by UV–vis absorptions peaking around 360 nm and exhibit a negative solvatochromism. An analysis of the kinetics of the zwitterion formation was performed for three Michael acceptors (acrylonitrile, methyl acrylate, and acrylamide) in two different solvents (chloroform and methanol). The results revealed the proton transfer step necessary to stabilize the initially formed carbanion as the rate-determining step. A preorganization of the carbonyl bearing Michael acceptors allowed for reasonable fast direct proton transfer from the phenol in aprotic solvents. In contrast, acrylonitrile, not capable of forming a similar preorganization, is hardly reactive in chloroform solution, while in methanol the corresponding phosphonium phenolate is formed.
Keywords: Lewis-base catalysis; Michael acceptor reactivity; phospha-Michael reaction; phosphonium phenolate zwitterion